2020
DOI: 10.3329/imcjms.v13i2.45275
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypothyroidism in different occupational groups of Bangladeshi population

Abstract: Background and aims: Hypothyroidism is a common global endocrine disorder. The magnitude of hypothyroidism at community level in Bangladesh is unknown except some clinic-based studies. The present study was undertaken to determine the prevalence of hypothyroidism in different occupational groups of Bangladeshi population and to assess the risks related to it. Study design: Three occupational groups (house-wives, college students, rickshaw-pullers) of native Bangladeshi population were purposively selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, there is no nationally representative population-based data regarding the prevalence of thyroid disorders among individuals of Bangladesh. A recent facility-based study including a few occupations group reported that almost 7% of the individuals had hypothyroidism ( 3 ). Similarly, in India, a neighboring south-east Asian country reported a high prevalence of thyroid disorders, almost 20% and hypothyroidism being the most common form of thyroid disorder ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no nationally representative population-based data regarding the prevalence of thyroid disorders among individuals of Bangladesh. A recent facility-based study including a few occupations group reported that almost 7% of the individuals had hypothyroidism ( 3 ). Similarly, in India, a neighboring south-east Asian country reported a high prevalence of thyroid disorders, almost 20% and hypothyroidism being the most common form of thyroid disorder ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, two studies investigating clinical practice patterns in the management of primary hypothyroidism ( 12 ) and Graves’ disease ( 13 ) demonstrated both alignment and focal divergence from the available clinical practice guidelines. Despite having a high burden of patients suffering from thyroid disorders in Bangladesh ( 3 , 14 , 15 ), there is hardly any study investigating the practice pattern of physicians for management of these disorders. Moreover, following the appropriate guideline for all the time in a resource poor setting like Bangladesh is not always feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse goiter has the highest incidence of 7.35%, followed by subclinical (6.59% to 15%) and clinical hypothyroidism (4.97%) [4,5]. A recent study from Bangladesh has reported the prevalence of hypothyroidism as 7% in different occupational groups [6] and its rate is 48% among the entire thyroid disorders [7]. Therefore, a significant number of the population is suffering from hypothyroidism that requires thyroid hormone replacement therapy.…”
Section: Introductionmentioning
confidence: 99%